Pengaruh Modal Usaha Dan Penjualan Terhadap Laba Kotor Usaha Pada Perusahaan CV. Korea Motor Surabaya - Benedictus Ocsa Christian (Pusat Riset dan Inovasi Nasional, 2026)
This research project seeks to develop and analyse the numerous effects of the variable Sales (X_1) and Working Capital (X_2) on the Gross Profit (Y) of CV. KOREA MOTOR. To study the financial interplay of these variables, the researcher utilises multiple linear regression as the primary technique and will also use correlation as an ancillary technique to measure the financial distance of the variables. To maintain the scientific accuracy of the results, the analyst will institute regression, more specifically, the t-test to measure partial (individual) effects) and the f-test to measure the joint (simultaneous) effects of the independent variables.The empirical results of the study indicate that Profitability is the dependent variable that is affected by the values of the two independent variables, Sales, and Working Capital. The Gross Profit of CV. KOREA MOTOR is also affected by these two independent variables. Hence, this research serves to reinforce the managerial concept that improving the value of Sales in conjunction with the effective management of Working Capital will increase the value of the Gross Profit of the company. Therefore, the outcome of this research will be applied as the basis for management to make financial decisions and for the company to progress.